2017
DOI: 10.1002/ps.4611
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between weed dormancy and herbicide rotations: implications in resistance evolution

Abstract: It is suggested that selection for late germinating seed cohorts is significantly associated with herbicide resistance in some cropping systems. In turn, it is conceivable that rotating herbicide modes of action selects for populations with mutations for increased secondary dormancy, thus partially overcoming the delaying effect of rotation on resistance evolution. Modified seed dormancy could affect management strategies - like herbicide rotation - that are used to prevent or control herbicide resistance. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…In one, researchers used a crossing design to homogenize the genetic background and found that A. myosuroides individuals with the Gly2078 ACCase resistance allele germinated earlier than wild-type individuals from the same genetic line (without the resistance allele). In comparison, lineages with a different resistance allele, Leu1781, exhibited delayed germination compared with wild-type (D elye et al, 2013b; Darmency et al, 2017). In the context of the Gly2078 allele, selection via herbicides should lead to the evolution of early germinators.…”
Section: Do Trait Trade-offs Constrain Evolution?mentioning
confidence: 99%
“…In one, researchers used a crossing design to homogenize the genetic background and found that A. myosuroides individuals with the Gly2078 ACCase resistance allele germinated earlier than wild-type individuals from the same genetic line (without the resistance allele). In comparison, lineages with a different resistance allele, Leu1781, exhibited delayed germination compared with wild-type (D elye et al, 2013b; Darmency et al, 2017). In the context of the Gly2078 allele, selection via herbicides should lead to the evolution of early germinators.…”
Section: Do Trait Trade-offs Constrain Evolution?mentioning
confidence: 99%
“…Thus, if this delayed sowing date is maintained for a number of years, a more dormant weed seed‐bank population will arise. As previously commented, selection for a higher level of dormancy due to selective pressure associated with pre‐sowing or early control practices has been reported by many authors …”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 72%
“…As for many others weed adaptive traits, agricultural practices also exert a strong selection on dormancy characteristics or levels . Preferable dormancy responses are those that allow weeds to survive in agroecosystems.…”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 99%
“…Much less is understood about responses to selection pressures other than herbicides, although there is increasing evidence in the literature for weed adaptation to non‐chemical control. For instance, there are many examples of within‐population variation in, and artificial selection for, seed dormancy (see references in Darmency et al ., ), including the observation that populations of Lolium rigidum in Australia delay germination in response to intensive cropping (Owen et al ., and references therein). There is also concern about the selection for shorter plants or earlier seed shedding in response to harvest weed seed control (HWSC, Walsh et al ., ).…”
Section: Introductionmentioning
confidence: 99%